PENGARUH FILSAFAT IDEALISME DAN REALISME DALAM PRAKTIK MANAJEMEN PENDIDIKAN - Sahilan, Sahilan; Megawati, Devi; Rahayu, Marlina (STKIP Pesisir Selatan, 2025)
As a process of managing resources to achieve educational goals, management practices are not only influenced by theory and policy, but also by the philosophical foundations that underlie views on humans, knowledge, and the purpose of life. The philosophy of idealism places ideas, values, and ideals at the center of all educational processes. Education is seen as an effort to humanize people through the formation of character and morality. This study aims to analyze the influence of idealism and realism philosophy in educational management practices, particularly in the aspects of planning, organizing, implementing, and supervising in the school environment. This study uses a descriptive qualitative approach with a literature study method. Data were collected from various relevant educational philosophy and management literature, then analyzed conceptually. The results of the study indicate that idealism philosophy influences the formation of a noble educational vision oriented towards character building, while realism philosophy provides direction for educational management based on facts, logic, and efficiency. The conclusion of this study shows that the integration of idealism and realism approaches can create holistic educational management practices, balanced between values and reality, and able to answer the challenges of contemporary educational dynamics.